2007
DOI: 10.1136/gut.2006.100628
|View full text |Cite
|
Sign up to set email alerts
|

Branch-duct intraductal papillary mucinous neoplasms of the pancreas: to operate or not to operate?

Abstract: Background: Branch-duct intraductal papillary mucinous neoplasms (BD-IPMNs) of the pancreas are reported to be less aggressive than the main-duct type. Hence, less aggressive treatment has been proposed for the former. Aim: To evaluate the effectiveness of a follow-up protocol for BD-IPMNs. Design: Prospective study. Patients who presented malignancy-related parameters (size .3.5 cm, nodules, thick walls, carbohydrate antigen 19.9 level .25 U/l, recent-onset or worsened diabetes) and/or complained of symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
199
2
13

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(221 citation statements)
references
References 35 publications
7
199
2
13
Order By: Relevance
“…In most series, the median age of patients at the diagnosis is 65-70 years [6,[8][9][10][11][12][13][14][15][16][17][18][19] . However, while a few studies made a clear distinction between MD-IPMNs and BD-IPMNs, most series include both subgroups.…”
Section: Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In most series, the median age of patients at the diagnosis is 65-70 years [6,[8][9][10][11][12][13][14][15][16][17][18][19] . However, while a few studies made a clear distinction between MD-IPMNs and BD-IPMNs, most series include both subgroups.…”
Section: Characteristicsmentioning
confidence: 99%
“…By contrast, in BD-IPMNs the frequency of malignancy is significantly lower (between 6% and 46%, with a mean of 25%) and that of invasive cancer ranges from 0 to 30% (mean of 15%) [6,8,9,[10][11][12][13][14][15][16] . In the combined experience of Massachusetts General Hospital and University of Verona, 145 patients underwent surgical resection for BDIPMNs [9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether or not an exact diagnosis is achieved may not turn out to be as important as the risk stratification based on imaging characteristics. A few recent prospective long-term follow-up studies showed that patients with presumed BD-IPMN in the absence of concerning radiographic features can be safely followed [15][16][17]. More importantly, the patients that developed suspicious radiologic findings (e.g.…”
mentioning
confidence: 99%
“…More importantly, the patients that developed suspicious radiologic findings (e.g. mural nodules or increase in cyst size) during close follow-up underwent surgical resection and none had invasive cancer [15][16][17].…”
mentioning
confidence: 99%